Acoustic impedance-based surface acoustic wave chip for gas leak detection and respiratory monitoring - Baile Cui; Wen Wang; Lina Cheng; Jing Jin; Anyu Hu; Zixuan Ren; Xufeng Xue; Yong Liang (Communications Engineering)
Abstract Acoustic impedance enables many interesting acoustic applications. However, acoustic impedance for gas sensing is rare and difficult. Here we introduce a micro-nano surface acoustic wave (SAW) chip based on the acoustic impedance effect to achieve ultra-fast and wide-range gas sensing. We theoretically established the relationship between surface load acoustic impedance and SAW attenuation, and analyzed the influence of acoustic impedance on acoustic propagation loss under different gas/humidity media. Experimental measurements reveal that the differences in acoustic impedance generated by different gases trigger different acoustic attenuation, and can achieve wide-range (0–100 v/v%) gas monitoring, with ultra-fast response and recovery speeds reaching sub-second levels (t 90 < 1 s, t 10 < 0.5 s) and detection limit of ~1 v/v%. This capability can also be perfectly utilized for human respiratory monitoring, accurately reflecting respiratory status, frequency, and intensity. Consequently, the SAW chip based on the acoustic impedance effect provides a new solution for in-situ detection of gas leaks and precise monitoring of human respiration.